2017
DOI: 10.18632/oncotarget.18967
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony stimulating factor treatment in non-alcoholic fatty liver disease: beyond marrow cell mobilization

Abstract: Protective effects of granulocyte colony stimulating factor (G-CSF) in acute liver injury via marrow cell mobilization have been reported in several studies. But exact mode of action and optimal protocol of G-CSF has been still doubt in chronic disease. Here we investigated mode of action and optimization of G-CSF as a treatment for non-alcoholic fatty liver disease (NAFLD). Various doses of conventional G-CSF (30 μg/kg once weekly, once daily for 5 days, twice weekly) and long acting G-CSF (30 μg/kg once a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Protective effects of G‐CSF on liver injury and damage have been noted in the literature both clinically and preclinically (53). Previously, both long‐acting and conventional G‐CSF supplementation was shown to be beneficial in mitigating liver cell apoptosis and intrahepatic fat accumulation (54). Perhaps a resistance to reduction, or conservation, of serum G‐CSF levels across treatment groups was protective in female offspring and supported healthier liver phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Protective effects of G‐CSF on liver injury and damage have been noted in the literature both clinically and preclinically (53). Previously, both long‐acting and conventional G‐CSF supplementation was shown to be beneficial in mitigating liver cell apoptosis and intrahepatic fat accumulation (54). Perhaps a resistance to reduction, or conservation, of serum G‐CSF levels across treatment groups was protective in female offspring and supported healthier liver phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of Akt in the development of NAFLD is still controversial because of paradoxical results showed by different studies. Briefly, some studies found an obvious activation of sterol regulatory element binding protein 1c (SREBP-1c) followed by Akt activaiton, which promoted fat deposition in liver [ 14 ], while other studies revealed a distinct opposite role of Akt activation for protecting against hepatic steatosis [ 15 , 16 ]. Although no consistent view was achieved on this issue, it did indicate an important role of Akt in the pathogenesis of NAFLD at least.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 This effect might be, at least partly, immune cell-independent as hepatocytes also express the G-CSF receptor (csf3r). 41 In vitro exposure of HepG2 cells to saturated fatty acids decreased cell viability and increased csf3r expression. G-CSF treatment was associated with increasing cell proliferation, reduced reactive oxygen species production, and lipotoxicity.…”
Section: The Rational Of Using G-csf To Treat End-stage Liver Diseasementioning
confidence: 99%
“…41 G-CSF has been tested in various rodent models of liver injury (►Table 1), where it demonstrated pleiotropic effects, reducing fibrosis in models of chronic liver injury, 42 mitigating liver injury in models of acute liver failure, [43][44][45][46] activating liver progenitor cells after partial hepatectomy, 47 and reducing lipid accumulation and lipotoxicity in models of nonalcoholic fatty liver disease. 41,48 In rat models of acute liver failure, hematopoietic stem cells mobilized by G-CSF could be detected in liver tissue and were associated with a decrease in liver inflammation and an increase in hepatocyte mitotic activity, suggesting a positive effect on tissue repair. Untreated rodents had a low survival rate of 25% 18 hours after induction of acute liver failure but that rate increased to 60% (p < 0.001) with G-CSF.…”
Section: The Rational Of Using G-csf To Treat End-stage Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation